AB0541 IMPROVED SURVIVAL IN PATIENTS WITH GIANT CELL ARTERITIS: A POPULATION-BASED COHORT STUDY. (2nd June 2020) - Garvey, T.; Crowson, C. S.; Koster, M.; Matteson, E.; Warrington, K. J.
Abstract : Background: In previous studies patients with giant cell arteritis (GCA) have had survival rates that are similar to the general population. Objectives: To investigate survival trends and cause-specific mortality in patients diagnosed with GCA over a 60-year period. Methods: We assembled a population-based incidence cohort of patients with GCA diagnosed between 1950 and 2009. All patients were included if they met the American College of Rheumatology (ACR) 1990 Criteria for the Classification of GCA. Patients diagnosed between 2000 and 2009 could also be included if they met the following criteria: age greater than or equal to 50 years, elevated inflammatory markers, and radiographic evidence of large-vessel vasculitis attributed to GCA. A non-GCA comparison cohort was assembled from the same underlying population for each patient with GCA. Patients were followed until death, last contact, or December 31 st, 2018. Survival trends were analyzed by grouping patients into the following categories according to year of GCA diagnosis: Group A 1950-1979; Group B 1980-1989; Group C 1990-1999; and Group D 2000-2009. Mortality rates were estimated using the Kaplan-Meier method and were compared with expected mortality rates for persons of the same age, sex, and calendar year, as estimated by regional population life tables. Cause-specific mortality was obtained from death certificates for patients in both cohorts. The causes were grouped according to ICD-9 chapters and hazard ratios were estimated against the non-GCA comparators. Results: The study population included 245 incident cases of GCA: 194 (79%) women and 51 (21%) men with mean age (±SD) of 76.2 (±8.3) years and median follow-up of 10.6 years. There was no overall difference in survival between the GCA cohort and the general population. The 2-, 5-, and 10-year survival rates (95% CI) were 89% (86, 93), 76% (70, 81), and 56% (50, 63) respectively with a standardized mortality ratio of 0.99 (0.86, 1.14). The standardized mortality ratios for Groups A, B, C, and D were 0.83 (0.57, 1.17), 0.92 (0.63, 1.3), 1.21 (0.85, 1.69), 0.70 (0.50, 0.95), respectively. The overall all-cause mortality adjusted for age, sex, and calendar-year was similar between the GCA patients and their comparators with a hazard ratio of 1.03 (0.84, 1.24). Mortality due to neoplasms was significantly lower in the GCA cohort with a hazard ratio of 0.53 (0.3, 0.92). Other cause-specific mortalities were not significantly different between the groups. Conclusion: In this population-based cohort of patients with GCA diagnosed over a 60-year period, the survival of patients diagnosed in recent years was significantly better than that of the general population. The explanation for this novel finding is unclear, but likely to be multifactorial. In this study the number of deaths due to neoplasm in the GCA group was significantly lower. References: [1]Chandran AK, et al. Incidence of Giant Cell Arteritis in Olmsted County, Minnesota, over a 60-year period 1950-2009. Scand J Rheumatol. 2015;44(3):215-218. [2]Mohammad A. et al. Rate of comorbidities in Giant Cell Arteritis: A Population-based Study. J Rheumatol. 2017;44(1):84-90. [3]Salvarani C. et al. Reappraisal of the epidemiology of giant cell arteritis in Olmsted County, Minnesota, over a fifty-year period. Arthritis Rheum. 2004;51(2):264-8. Acknowledgments: This study was made possible using the resources of the Rochester Epidemiology Project, which is supported by the National Institute on Aging of the National Institutes of Health (NIH) under Award Number R01 AG034676, and CTSA Grant Number UL1 TR000135 from the National Center for Advancing Translational Sciences (NCATS), a component of the NIH. The content is solely the responsibility of the authors and does not necessarily represent the official views of the NIH. Disclosure of Interests: Thomas Garvey: None declared, Cynthia S. Crowson Grant/research support from: Pfizer research grant, Matthew Koster: None declared, Eric Matteson Grant/research support from: Pfizer, Consultant of: Boehringer Ingelheim, Gilead, TympoBio, Arena Pharmaceuticals, Speakers bureau: Simply Speaking, Kenneth J Warrington: None declared